2020
DOI: 10.3390/ijms21072283
|View full text |Cite
|
Sign up to set email alerts
|

Flotillins: At the Intersection of Protein S-Palmitoylation and Lipid-Mediated Signaling

Abstract: Flotillin-1 and flotillin-2 are ubiquitously expressed, membrane-associated proteins involved in multifarious cellular events from cell signaling, endocytosis, and protein trafficking to gene expression. They also contribute to oncogenic signaling. Flotillins bind the cytosolic leaflet of the plasma membrane and endomembranes and, upon hetero-oligomerization, serve as scaffolds facilitating the assembly of multiprotein complexes at the membrane–cytosol interface. Additional functions unique to flotillin-1 have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 139 publications
(318 reference statements)
1
62
0
Order By: Relevance
“…Similarly to PHBs, flotillins exist as 2 isoforms, flotillin-1 and flotillin-2, which are ubiquitously expressed scaffold proteins involved in various aspects of cell signaling, cytoskeleton remodeling, endocytosis, release of extracellular vesicles and protein trafficking. 43 To fulfill these functions, they directly interact with several proteins, including the EGF receptor, the kinases Lyn, Fyn, Lck, cRAF, MEK1, ERK2, cRAF, MEK1/2, ERK1/2, KSR1 the small GTPases Gαq, Rab11, β-catenin, γ-catenin, E-cadherin, N-cadherin, the adaptor protein ArgBP2, the adapter protein SORBS1 /CAP/Ponsin, the E3 ubiquitin-protein ligase Cbl, α-actinin or F-actin. As far as we know, no small molecules targeting flotillins has been discovered yet, but such agents could display interesting effects to treat several types of diseases, including cancers, immunological, cardiac and neurodegenerative disorders.…”
Section: Flotillinsmentioning
confidence: 99%
“…Similarly to PHBs, flotillins exist as 2 isoforms, flotillin-1 and flotillin-2, which are ubiquitously expressed scaffold proteins involved in various aspects of cell signaling, cytoskeleton remodeling, endocytosis, release of extracellular vesicles and protein trafficking. 43 To fulfill these functions, they directly interact with several proteins, including the EGF receptor, the kinases Lyn, Fyn, Lck, cRAF, MEK1, ERK2, cRAF, MEK1/2, ERK1/2, KSR1 the small GTPases Gαq, Rab11, β-catenin, γ-catenin, E-cadherin, N-cadherin, the adaptor protein ArgBP2, the adapter protein SORBS1 /CAP/Ponsin, the E3 ubiquitin-protein ligase Cbl, α-actinin or F-actin. As far as we know, no small molecules targeting flotillins has been discovered yet, but such agents could display interesting effects to treat several types of diseases, including cancers, immunological, cardiac and neurodegenerative disorders.…”
Section: Flotillinsmentioning
confidence: 99%
“…Flotillin-1 is preferentially associated with flotillin-2 in hetero-oligomeric complexes, forms membrane microdomains that serve as scaffolds facilitating the assembly of multiprotein complexes at the membrane-cytosol interface ( Zhao et al, 2011 ; Kwiatkowska et al, 2020 ). It was observed that flotillin-1 is associated with tyrosine-protein kinase Lyn and enhances its activity ( Kato et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Flotillins bind the inner leaflet of a plasma membrane raft and serve as scaffolds facilitating the assembly of multiprotein complexes. Flotillin-1 and flotillin-2 have the same domain architecture, comprising two domains: the N-terminal SPFH domain and the C-terminal flotillin domain [98]. The SPFH and flotillin domains mediate inner membrane binding and oligomerization of flotillins, respectively.…”
Section: G Protein-coupled Receptors (P2y1 P2y12 Cxcr4)mentioning
confidence: 99%
“…Sphingosine binding is mediated by the SPFH domain of flotillins, but the exact identities of the hydrophobic sequences of the flotillins involved are not known. Flotillins also interact with numerous signaling proteins such as receptors, protein kinases, G proteins, and adaptors [98]. Therefore, flotillin-based microdomains can serve as platforms mediating the formation of multiprotein complexes and transmembrane signal transduction at the plasma membrane.…”
Section: G Protein-coupled Receptors (P2y1 P2y12 Cxcr4)mentioning
confidence: 99%